2017
DOI: 10.2319/121216-890.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional positional assessment of glenoid fossae and mandibular condyles in patients with Class II subdivision malocclusion

Abstract: Objectives: To test the null hypotheses that the positions of the glenoid fossae and mandibular condyles are identical on the Class I and Class II sides of patients with Class II subdivision malocclusion. Materials and Methods: Retrospective three-dimensional (3D) assessments of the positions of the glenoid fossae and mandibular condyles were made in patients with Class II malocclusion. Relative to a fiducial reference at the anterior cranial base, distances from the glenoid fossae and condyles were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Overlapping of adjacent structures and complex anatomy causes difficulty in assessing TMJ by conventional imaging. 23 CBCT allows reconstruction of images in planes parallel and perpendicular to the long axis of the condyle, enabling thorough assessment of its position within the glenoid fossa. This also allows effective evaluation of the integrity of the bony structures.…”
Section: Temporomandibular Jointmentioning
confidence: 99%
“…Overlapping of adjacent structures and complex anatomy causes difficulty in assessing TMJ by conventional imaging. 23 CBCT allows reconstruction of images in planes parallel and perpendicular to the long axis of the condyle, enabling thorough assessment of its position within the glenoid fossa. This also allows effective evaluation of the integrity of the bony structures.…”
Section: Temporomandibular Jointmentioning
confidence: 99%
“…The CBCT allowed observing a mandibular asymmetry, which was not demonstrated by previous analysis. Furthermore, de Mattos et al [17] showed a difference between the glenoid fossa of the Class II side compared to the contralateral one of the Class I side. Li et al [18] used CBCT analysis in combination with dental cast analysis and functional factors observation investigated by determination of the centric relation (CR)-centric occlusion (CO) discrepancies.…”
Section: Introductionmentioning
confidence: 98%
“…Li et al 25 also compared Class II subdivision cases with Class I malocclusions and showed that the asymmetry was associated with distal positioning of the glenoid fossa. de Mattos et al 26 supported that Class II subdivision malocclusions present with asymmetric glenoid fossa, with a distally and laterally positioned glenoid fossa on the Class II side. Sanders et al 24 studied CBCTs of Class II subdivisions and concluded that the aetiology is primarily due to an asymmetric mandible that is shorter and positioned posteriorly on the Class II side.…”
Section: Introductionmentioning
confidence: 99%